Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3758/app.72.5.1261
|View full text |Cite
|
Sign up to set email alerts
|

Increased hedonic differences despite increases in hedonic range

Abstract: Viewing hedonically negative paintings increased the hedonic ratings of subsequently viewed test paintings (positive hedonic contrast; Experiment 1) and also increased the degree of preference between the test paintings (Experiments 2 and 3). This result differs from the reduction in hedonic preference (hedonic condensation) that accompanies negative hedonic contrast. It also differs from the reduction in perceived differences that usually accompanies expansion of stimulus range and that is predicted by numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…For example, evaluations of pieces of music increase or decrease depending on whether previously heard pieces sounded bad or good, respectively (Parker et al, 2008). Similar hedonic-contrast effects are observed with tastes (Zellner et al, 2003), pictures of birds (Zellner et al, 2003), paintings (Dolese et al, 2005; Zellner et al, 2010), and the degree to which people are considered physically attractive (Kenrick and Gutierres, 1980). …”
Section: Introductionmentioning
confidence: 63%
“…For example, evaluations of pieces of music increase or decrease depending on whether previously heard pieces sounded bad or good, respectively (Parker et al, 2008). Similar hedonic-contrast effects are observed with tastes (Zellner et al, 2003), pictures of birds (Zellner et al, 2003), paintings (Dolese et al, 2005; Zellner et al, 2010), and the degree to which people are considered physically attractive (Kenrick and Gutierres, 1980). …”
Section: Introductionmentioning
confidence: 63%
“…Subjects readily apprehend the use of a scale of this sort with no special instruction; this was particularly useful in the informal settings in which data collection occurred. This sort of 10-point scale has been used to assess hedonic differences in Zellner et al (2010). As the subject was taking the headphones and was about to put them on, the experimenter said one of three things, defining the three conditions of the experiment:…”
Section: Methodsmentioning
confidence: 99%
“… Schellenberg et al (2012) showed that emotional contrasts between adjacent musical stimuli intensify listeners’ emotional responses, and the intensified emotional responses tend to increase listeners’ appreciation because music evoking strong emotions is preferred by listeners. Notably, hedonic-contrast effects have been particularly associated with responses to stimuli that are evaluated esthetically ( Parducci, 1995 ; Dolese et al, 2005 ; Zellner et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%